Mutinous memories : a subjective history of French military protest in 1919 - Perry, Matt, 1967- (Manchester University Press, 2019)
This book explores the eight-month wave of mutinies that struck the French infantry and navy in 1919. Based on official records and the testimony of dozens of participants, it is the first study to try to understand the world of the mutineers. Examining their words for the traces of sensory perceptions, emotions and thought processes, it reveals that the conventional understanding of the mutinies as the result of simple war-weariness and low morale is inadequate. In fact, an emotional gulf separated officers and the ranks, who simply did not speak the same language. The revolt entailed emotional sequences ending in a deep ambivalence and sense of despair or regret. Taking this into account, the book considers how mutineer memories persisted after the events in the face of official censorship, repression and the French Communist Party's co-option of the mutiny.